Lived experiences of diabetes self-management in North Shoa, Ethiopia: A phenomenological inquiry - Akine Eshete; Abera Lambebo; Lemma Getacher; Tewodros Kifleyohans; Yibeltal Assefa; Hendry Van Der Heever; David D. Mphuthi (PLoS ONE, 2026)
Background Despite government efforts, diabetes self-management remains inadequate for many patients due to complex barriers. Understanding the lived experiences and barriers to self-care practices is essential for facilitating behavior change and achieving personal health goals for improved diabetes management. Therefore, this study aimed to explore the lived experiences and barriers faced by individuals living with diabetes in adhering to their self-care practices. Methods This phenomenological study was carried out in the North Shoa Zone from 1 to 30 July 2024. The study consisted of a total of 25 participants, 20 diabetic patients and five healthcare informants from four districts. The participants were selected using maximum variation sampling method, considering factors such as age, sex, marital status, occupation, and type of diabetes. A pretested interview guide was used to gather the data, which were then recorded, transcribed, and analyzed with ATLAS.Ti software. A thematic framework was applied to identify key codes, subthemes, and main themes associated with diabetes self-care and the barriers to its practice. Results Diabetes self-management behaviors were found to be insufficient, mainly due to barriers at the individual, interpersonal, and community levels. Despite high adherence to prescribed medications intake among most patients, many still have inadequate practices in self-blood glucose monitoring, diet, regular physical activity, and foot care. Key barriers included limited knowledge of self-care, socioeconomic constraints, lack of guidance, low motivation, stress, limited social support, cultural influences, and poor access to resources. Conclusions Diabetes self-care was inadequate due to several challenging barriers. To improve these practices, it is crucial to integrate behavioral change interventions, provide mental health support, implement stress management strategies, and foster community partnerships to address barriers comprehensively at all levels.